2020
DOI: 10.1007/s40315-020-00350-9
|View full text |Cite
|
Sign up to set email alerts
|

Crouzeix’s Conjecture and Related Problems

Abstract: Crouzeix's conjecture asserts that, for any polynomial f and any square matrix A, the operator norm of f (A) satisfies the estimate f (A) ≤ 2 sup{| f (z)| : z ∈ W (A)}, (1) where W (A) := { Ax, x : x = 1} denotes the numerical range of A. This would then also hold for all functions f which are analytic in a neighborhood of W (A). We provide a survey of recent investigations related to this conjecture and derive bounds for f (A) for specific classes of operators A. This allows us to state explicit conditions th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…We conclude this section by remarking that the ideas behind Theorems 3.1 and 3.2 are developed further in [9]. In particular, it is shown in [9, Theorem 4.5] that, under the hypotheses of Theorem 3.2, there exists a unique probability measure µ on ∂D such that, for all continuous functions h on D that are holomorphic on D, we have…”
Section: Properties Of Exceptional Matricesmentioning
confidence: 93%
“…We conclude this section by remarking that the ideas behind Theorems 3.1 and 3.2 are developed further in [9]. In particular, it is shown in [9, Theorem 4.5] that, under the hypotheses of Theorem 3.2, there exists a unique probability measure µ on ∂D such that, for all continuous functions h on D that are holomorphic on D, we have…”
Section: Properties Of Exceptional Matricesmentioning
confidence: 93%
“…(which is equivalent to the inclusion W (T ) ⊂ Ω) has served as a basis for establishing K-spectral estimates for W (T ); an approach originally due to Delyon and Delyon [18], it was further refined by Crouzeix in [14] and culminated in the Crouzeix-Palencia paper [13] (see also [26], [7] and the recent preprint [27] for further developments), where it was shown that W (T ) is always a (1 + √ 2)-spectral set for any T ∈ B(H). More recently, the study of K-spectral estimates through the contractivity of S Ω,2 has expanded beyond convex domains (see [8], [16]).…”
Section: Introductionmentioning
confidence: 99%